Biology, distribution and effect of selected insecticides against whitefly (Trialeurodes Vaporariorum Westwood and Bemisia Tabaci Gennadius) on brinjal (Solanum melongena L.) / Mohd Rasdi Zaini - Zaini, Mohd Rasdi (2005)
Whitefly, Trialeurodes vaporariorum (Westwood), a common insect that feeds on plants, belongs to the family Aleyrodidae of the order Homoptera. Many farmers are not interested to grow brinjal after they have gone through some bad experience due to whitefly infestations which have resulted in a total yield loss and affected the marketability of brinjal fruits. At present, information on the biology and population dynamics of whiteflies locally on brinjal is still lacking. Therefore, these studies are indeed appropriate to generate a comprehensive understanding on the insect biology, which could support an effective pest management programme and crop improvement strategy. The present studies involved field and laboratory experimentations, trials and observations on the life cycle of whitefly, its fecundity, its host preference, its specific parasitoids and its mortality rates as affected by some common insecticides. The host crops used were brinjal, tomato and tobacco plants, which are considered as high value crops. The studies were conducted at the MARDI station, the Cameron Highlands, Field Laboratory of the Faculty of Applied Science, Universiti Teknologi MARA, Shah Alam. The study on the life cycle of whitefly showed that, its developmental stages covered the eggs, larvae (instars I, II, and III), pupae, and adults. The eggs hatched within 6 to 9 days after oviposition with an average 7.6 days. In the laboratory conditions with the temperature of 24.0±2ºC, the total developmental period of whitefly, from the eggs to adults was 26.1 days and from eggs to eggs was 50.7 days. It was found that the maximum longevity recorded for the adult whiteflies on the average, was 25.3 days when they were supplied with honey and young leaves of brinjal, followed by 24.7 days when they were supplied with only brinjal leaves. An average of 102 eggs was laid in 26 days by one female adult. The study showed that whitefly had no significant preferences to host crops such as brinjal, tomato, and tobacco which belong to same family of Solanaceae. Macrolophus caliginosus, a predatory bug commonly found in the Cameron Highlands, significantly contributed to the control of whitefly. The total mean developmental period for predators from oviposition until the emergence of adults was 27.6 days. The whitefly larvae were killed and fed randomly by the adult predators daily. The daily predation rate of the predators has been enumerated with mean a range from 5.3 to 6.3 larvae per day. It showed that predators attacked from the first larval stage until pupal stage. The total mean whitefly larvae killed by adult predators was 5.8 larvae per day. The presence of whitefly larvae could increase the survival rate or life span of predators. It was also found that the distribution of whitefly larvae on brinjal plants covered all the plant strata except for the upper stratum. The populations of whitefly were aggregated (Taylor’s Power Law Calculate) in first and second cropping of brinjal plants. Generally, the nymph predators were found on the upper and middle strata of the tomato plants. Among the common insecticides being tested for their effectiveness in controlling whitefly, it was observed that avermectin gave the best control. It recorded the lowest rate of survival of whitefly larvae compared with the control and this was followed by white oil, buprofezin, lambda cyhalothrin, and cyromazin. The study suggested that the effective chemical treatment with insecticides such as avermectin, buprofezin, and white oil would be to spray the crops at 7 days’ intervals within 30 to 40 days (4 to 6 times of application) that whitefly takes to completion its life cycle. It would be desirable if any potential insecticide could be used in good combinations with some beneficial biological control agents such as Macrolophus caliginosus under the concept of integrated pest management programme. With a proper planning and timing of application of insecticides together with the release of ii known biological control agents, it might result in the best means of controlling whitefly. This also would give a great deal of contributions to the farmers in terms of reducing the cost of vegetable production whilst at the same time increasing the profit margins as well as reducing the toxic remains in the plants or the environment.